PENGARUH DIMENSI KEPEMIMPINAN INSTRUKSIONAL KEPALA SEKOLAH TERHADAP EFIKASI DIRI GURU - Karim, Mukhammad A; Rosminingsih, Erni; ., Soedjarwo (Inspiratif Pendidikan, 2020)
Current research about instructional leadership and teacher self-efficacy lacked how its variable constructed. They largely treated instructional leadership and teacher self-efficacy as a single construct and ignored dimension inside. Purpose of this research is to investigate effect dimension of instructional leadership on teacher self-efficacy’s dimension in Senior High School Kediri with 124 teachers as respondent gathered by cluster sampling technique. Principal Instructional Management Rating Scale (PIMRS) and Teacher Self Efficacy (TSES) are used as an instrument to measure these variables. Partial Least Squares (PLS) is used for data analysis. The result indicate that managing the instructional program and developing the school learning climate predict instructional strategies (R2= 0.31), defining the school mission and developing the school learning climate predict classroom management (R2= 0.29), and three dimension of instructional leadership predict student engagement (R2= 0.30). Finally, author suggested some recomendation for the future studies.